A Proposed Training Program for School Leaders in the Sultanate of Oman on the Planning Practices of the Kaufman Model in Light of the Needs and Challenges of Reality (Journal Of Educational and Psychological Researches, 2023)
The study aims to build a proposed training program for school leaders in the Sultanate of Oman on the planning practices of the Kaufman model in light of the needs and challenges of reality. It also aims to identify the challenges facing school leaders in practicing the stages of strategic planning. To achieve these objectives, the study adopted the descriptive approach due to its suitability to the nature of the study. A questionnaire was used to collect the needed data. The study sample included (225) individuals from school principals, their assistants and senior teachers in post-basic education in the Sultanate of Oman. After processing the data statistically, the study concluded that the reality of planning practices for school leaders in post-basic education came with a medium degree of practice. The results also showed the most important challenges facing school leaders in strategic planning practices, which were limited training programs dealing with strategic planning practices, lack of material and moral incentives for those in charge of preparing and implementing plans, and the scarcity of successful and approved models for strategic planning that clarify the general framework for planning. The researcher proposed a training program to school leaders in the Sultanate of Oman on the planning practices of the Kaufman model in light of the needs and challenges of reality